2003
DOI: 10.1128/jb.185.15.4432-4441.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation at thevlsELocus ofBorrelia burgdorferiwithin Ticks and Mice over the Course of a Single Transmission Cycle

Abstract: The Lyme disease spirochete, Borrelia burgdorferi, causes a persistent infection in the vertebrate host even though infected animals mount an active immune response against the spirochete. One strategy used by the spirochete to evade vertebrate host immunity is to vary the structure and expression of outer membrane antigens. The vlsE locus represents the best-studied example of antigenic variation in B. burgdorferi. During vertebrate host infection, recombination between the active vlsE locus and silent, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…Data from this report are consistent with previous studies that examined small parts of the infectious cycle. Ohnishi et al also noticed that the protein was expressed by very few (Ͻ1%) bacteria in midguts of unfed or partially fed nymphs (40). Indest et al observed some VlsE expression in flat nymph midguts but not after feeding commenced (23).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Data from this report are consistent with previous studies that examined small parts of the infectious cycle. Ohnishi et al also noticed that the protein was expressed by very few (Ͻ1%) bacteria in midguts of unfed or partially fed nymphs (40). Indest et al observed some VlsE expression in flat nymph midguts but not after feeding commenced (23).…”
Section: Discussionmentioning
confidence: 94%
“…The spirochete synthesizes little or no VlsE when colonizing the midgut of a vector tick nymph (23,40) but does make that protein during mammalian infection (14,20,21,29,(31)(32)(33)35). However, prior to this study, the complete pattern of VlsE synthesis in vivo had not been examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An ELISA (IR6) using a peptide derived from the VlsE protein of Borrelia has demonstrated greater specificity in the detection of Lyme disease than whole-cell ELISAs and has been approved for use by the FDA (19,23). However, C6, the peptide derived from VlsE, does not bind IgM particularly well, is derived from an antigen that is expressed only after infection is established (fewer than 1% of bacteria in the tick express VlsE, and transcription of the gene is suppressed prior to transmission of the bacteria), and the IR6 region of VlsE from which the peptide is derived has shown a greater degree of variability than originally thought (19,(23)(24)(25)(26). Though the IR6 assay represents a significant improvement, in terms of specificity, compared to the whole-cell ELISA (27), these concerns have precluded the use of the IR6 assay as a stand-alone diagnostic test for early Lyme disease.…”
mentioning
confidence: 99%
“…Nevertheless signals involved in recombination are unknown. It was found that the number of amino acid changes is signifi cantly higher in immunocompetent C3H mice than in SCID mice and this suggests an infl uence of selective pressure 114,115 .…”
Section: Outer Surface Protein Cmentioning
confidence: 99%